The legal status of refugee protection and state obligations in Uganda - Frank, Ahimbisibwe (Us-China Law Review, 2016)
Uganda is a host country to refugees from neighboring countries affected by conflicts and war. According to UNHCR, by the end of 2015, Uganda was the 8th and 3rd top refugee hosting country in the world and Africa respectively. It hosted around 512,968 refugees. Uganda was estimated to host around 810,000 refugees by the end of 2016. This raises the questions that as one of the top refugee hosting countries; are refugees legally protected in Uganda? What are the gaps existing in this legal framework? What legal obligations does Uganda have in refugee protection? This paper answers these questions by analyzing the existing refugee and human rights legal instruments to which Uganda is a signatory. The paper further makes reference to case law as evidence that states have obligations to protect refugees. In analyzing the legal framework, the existing gaps are identified. This paper argues that refugees in Uganda are protected by both refugee and human rights law. Refugee law protects refugees by virtue of their status as refugees who have crossed international borders and in need of international protection. Refugees are also protected by human rights law as individuals and human beings regardless of their status as refugees or aliens and wherever they have gone. Courts’ jurisprudence has confirmed that states have obligations to protect refugees
Keywords: Legal Status; Refugee Protection; State; Uganda